Bi-directional relation between effort‒reward imbalance and risk of neck-shoulder pain: assessment of mediation through depressive symptoms using occupational longitudinal data - Jaana I Halonen; Tea Lallukka; Marianna Virtanen; Naja Hulvej Rod; Linda L Magnusson Hanson (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: Bi-directional associations between perceived effort‒reward imbalance (ERI) at work and neck-shoulder pain have been reported. There is also evidence of associations between ERI and depressive symptoms, and between depressive symptoms and pain while the links between ERI, depressive symptoms and pain have not been tested. We aimed to assess whether depressive symptoms mediate the association between ERI and neck-shoulder pain, as well as the association between neck-shoulder pain and ERI. METHODS: We used prospective data from three consecutive surveys of the Swedish Longitudinal Occupational Survey of Health (SLOSH) study. ERI was assessed with a short version of the ERI questionnaire, and pain was defined as having had neck-shoulder pain that affected daily life during the past three months. Depressive symptoms were assessed with a continuous scale based on six-items of the (Hopkins) Symptom Checklist. Counterfactual mediation analyses were applied using exposure measures from 2010/2012 (T1), depressive symptoms from 2012/2014 (T2), and outcomes from 2014/2016 (T3), and including only those free of outcome at T1 and T2 (N=2876‒3239). RESULTS: ERI was associated with a higher risk of neck-shoulder pain [risk ratio (RR) for total effect 1.22, 95% confidence interval (CI) 1.00-1.48] and 41% of this total effect was mediated through depressive symptoms. Corresponding RR for association between neck-shoulder pain and ERI was 1.34 (95% CI 1.09-1.64), but the mediating role of depressive symptoms was less consistent. CONCLUSIONS: Depressive symptoms appear to be an intermediate factor in the relationship between ERI and neck-shoulder pain.